2018
DOI: 10.1016/j.gde.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and cellular mechanics of seeds

Abstract: Distinct plant seed/fruit structures evolved to support reproduction and dispersal in distinct environments. Appropriate biomechanical properties and interactions of the various seed compartments are indispensable to plant survival. Most seeds are dispersed in a dry state generated during seed development/maturation for which novel aspects of endosperm-embryo interaction were discovered. The various layers covering the embryo of a mature seed define the patterns of water uptake during germination. Their biomec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 56 publications
0
40
0
Order By: Relevance
“…It was shown that small heat shock proteins (HSP20s) were a group of stress-responsive proteins mainly expressed in the seed and flower [ 74 ]. The HSP20s were ATP-dependent small chaperons with molecular weight ranging from 15 kDa to 42 kDa [ 75 ]. Hsp20s could avert protein denaturation, and thus maintain cellular homeostasis during abiotic stresses [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that small heat shock proteins (HSP20s) were a group of stress-responsive proteins mainly expressed in the seed and flower [ 74 ]. The HSP20s were ATP-dependent small chaperons with molecular weight ranging from 15 kDa to 42 kDa [ 75 ]. Hsp20s could avert protein denaturation, and thus maintain cellular homeostasis during abiotic stresses [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Endosperm weakening À the classic story revitalized Endosperm weakening has been a major topic and is almost a classic story in seed germination research, which has been summarized and updated in review articles and textbooks (Nonogaki et al 2007;Bewley et al 2013;Nonogaki 2014;Steinbrecher and Leubner-Metzger 2018). The weakening of the secondary cell walls of the micropylar endosperm (ME) by hemicellulases, for example, endo-b-mannanase, has been particularly well documented in association with the changes in the secondary cell walls (Groot and Karssen 1987;Groot et al 1988;Toorop et al 1996).…”
Section: Seed Germinationmentioning
confidence: 99%
“…Seed germination is a complex process and we need to understand the underlying molecular, hormonal, and mechanical aspects [72]. The environment during seed production has major impacts on the behavior of progeny seeds [73].…”
Section: Adnormentioning
confidence: 99%
“…The environment during seed production has major impacts on the behavior of progeny seeds [73]. For that reason, the seed biology is considered the principal research topic for food security take into consideration the climate change [72].…”
Section: Adnormentioning
confidence: 99%